Diabetic Peripheral Neuropathy and its Determinants among Patients Attending a Tertiary Health Care Centre in Mangalore, India - D’Souza, Monisha (J Public Health Res, 2015)
BACKGROUND: The burden of diabetes mellitus (DM) is on the rise especially in developing countries like India. Due to its chronic nature DM tends to cause many debilitating complications and diabetic peripheral neuropathy (DPN) is one of them. The aim of this study is to determine the prevalence of DPN among patients attending a tertiary care hospital and to identify the determinants associated with it. DESIGN AND METHODS: A cross sectional study was conducted in Government Wenlock Hospital, Mangalore (India), during January-February 2014. A total of 208 patients with >5 year duration of DM were asked to respond to the patient history version of Michigan Neuropathy Screening Instrument (MNSI) and examinations were conducted after obtaining consent from them. The statistical analysis was done in terms of descriptive statistics and association between variables was tested using logistic regression test. RESULTS: The prevalence of DPN using the MNSI history version and MNSI examination were found to be 18.3% and 32.2% respectively. The major determinants associated with DPN were found to be male gender (OR: 2.7, CI: 1.4-5.1, P=0.001), smoking (OR: 5.8, CI: 1.9-17.3, P=0.001) and age >40 years (OR: 2.7, CI: 1.2-5.8, P=0.011). CONCLUSIONS: The burden of undetected DPN was found to be higher among diabetics, with an especially higher prevalence among males, smokers and those with long standing diabetes mellitus. Interventions in the form of early detection through routine screening, smoking cessation and regular follow up examinations would go a long way in reducing the burden of disability among diabetics and improve their quality of life significantly.